KARAKTERISASI ZEOLIT ALAM SELONG BELANAK LOMBOK SEBAGAI ADSORBEN DALAM PEMURNIAN ALKOHOL FERMENTASI - Hulyadi, Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2017)
NTB has a large zeolite potential with a zeolite content percentage of 190,405 tons. One area that has great potential is the Selong belanak Central Lombok precisely at coordinates 8o51'48.5 "S 116o10'62.0" E mull mullet. Utilization of zeolite Lombok area is only used as a mixture of animal feed because it has not done research on its potential. One potential zeolite is its ability as an absorbent. Alcohol fermentation has not been able to be an alternative as a solution to energy problems. Alcohol fermentation only produces alcohols of less than 30% purity. This is caused by acetic acid byproducts that make microbes in the fermentation process can not breed optimally. From these problems need to be performed zeolite characteristic for optimal utilization. The purpose of this research is to find out the characteristics of natural zeolite of Selong belanak Lombok as an adsorbent in purifying alcohol of fermentation. The method of this research is descriptive with data collecting technique performed by zeolite characterization including cation exchange capacity with Schollenberger method, surface area using methylene blue method, absorption using Iodometry titration method, zeolite water content using gravimetric method and alcohol concentration determined by specific gravity and instrument GC-MS. Based on the result of natural zeolite research, Selong belanak Lombok has characteristic with natural cation zeolite exchange capacity of Selong Belanaq Lombok for 14,0894 meq / 100 gram. The zeolite surface area is 16, 3537 m2 / gram. Absorption zeolite to iodium is relatively low at 2.9357%. water content obtained from natural zeolite Selong Belanaq Lombok is 7.74%. After use of various alcoholic distillate absorbent fermentation alcohol concentration was obtained 81.4%. Based on the findings of natural zeolite researchers mullet tubes need to be activated more optimally to produce alcohols with purity above 99%, as laden mixture material in gasoline.